Literatura de entretenimento: a atuação de blogueiros e youtubers no ciberespaço e a indústria do livro no Brasil - Melo, Maria Bethânia de Figueiredo (2019)
In LITERATURE OF ENTERTAINMENT: the performance of bloggers and youtubers in cyberspace and the book industry in Brazil intend to understand this new dynamic assumed by the Brazilian publishing market, as well as the participation of young "digital influencers" in the book market. The present research considers the work of bloggers and youtubers in cyberspace through their social networks and, in parallel with this, the entrance of these internauts into the universe of Entertainment Literature, filling a market niche lacking in publications, that of the adolescent consumer, with the publishing their own books, which contributes significantly to the achievement of the investment in the materiality of digital content. And also the relationship between followers / readers who start to consume more and more everything that is published by their "internet idols", which on the other hand stimulates the practice of reading. The purpose of this investigation is therefore to propose reflections on this new movement of printed textual production by young youtubers and bloggers and, in addition, to delve through the cibercaminhos to understand the transfigurations by which the industry of the printed book is passing in times of society digital. In order to reach the objectives proposed in this research, we decided to make as a methodological resource a bibliographical research (qualitative and quantitative) of printed books published by young digital influencers between January 2012 and December 2018, during which time we verified the publication of one hundred and fifty and nine books. The theoretical contribution of the research is focused on Giorgio Agamben (2009), Zigmunt Bauman (2001), Manuel Castells (2001), Nicholas Carr (2011), Roger Chartier (1999), Tom Chatfield (2012), Pierre Lévy (2010), Perrone-Moisés (2016), Katherine Hayles (2009), Henry Jenkins (2008), among others.